The Analysis of Business Model In Social Entrepreneurship (Open Society Conference, 2024)
Increasing public concern about current environmental conditions has led to many social entrepreneurship activities addressing environmental concerns as social goals. Indonesia's population has reached 267 million people, this population density has many problems related to the economy and social that transform many entrepreneurs to consider the concept of entrepreneurship that can contribute to social change. The combination of entrepreneurship with social goals is called social entrepreneurship. One of the elements that can be highlighted in social enterprise is its business model, enabling the company to create new and impactful value to consumers for achieving intended social mission. This study addresses the business model run by a social enterprise with a social mission for environmental sustainability, namely PT. Cleanomic Jaya Global and uses a qualitative method by describing the business model canvas for social entrepreneurship. The results of the study indicate that the company has implemented a business model canvas social for entrepreneurship. Keywords: social entrepreneurship, business model, environmental Sustainability, canvas business model